Olympic medal-winning leadership - Din, C.; Paskevich, D.; Gabriele, T.; Werthner, P.; Arnold, R.; Vella, S. (International Journal of Sports Science and Coaching, 2015)
The purpose of this qualitative research was to develop a detailed description of leadership in contemporary Canadian Olympic medalwinning sport to better understand how Olympic podium performances are developed. The integrated research model of Olympic podium performance acted as a theoretical framework and starting point for inquiry. Semi-structured personal interviews were conducted with a purposive sample of ten coaches and twelve athletes who together won gold or silver medals in the 2010 winter Olympic Games. The interview questions were designed to assess the theoretical framework of Olympic medal-winning leadership as well as allow for new themes to emerge from the interview process. Including both coach and athlete perspectives in this research created an opportunity for a nuanced portrait of leadership. Interpretive thematic analysis of the 22 interviews revealed three major themes. Leadership was found to be demanding, relational and solutionfocused for all the coaches and a strong consensus was found between the coach and athlete descriptions of leadership. Recommendations are suggested for future research and the development of effective coach leadership behaviours for coaches in the Olympic sport context.